A risk assessment study on work-related musculoskeletal disorders among dentists in Bhopal, India - Chetna Batham (Indian Journal of Dental Research, 2016)
Background: Work-related musculoskeletal disorders (WMSDs) are responsible for morbidity in many working populations, which are of multifactorial in origin and of global concern due to industrialization. Dentists as one of the health-care professionals are prone to develop these WMSDs. The study aims to determine the prevalence of WMSDs among dentists in Bhopal region and explores the various risk factors for the development of MSDs and WMSDs. Materials and Methods: This proposed study is a cross-sectional study conducted among dentists of two randomly selected dental colleges of Bhopal, India. A structured questionnaire was used to collect the demographic information, occupational history, risk factors, and ergonomic awareness with job task details. Prevalidated standardized tools such as quick exposure check list, rapid entire body assessment score sheet, and Nordic Musculoskeletal Questionnaire were also used. Data were entered in MS-Excel and analyzed through SPSS version 18. Results: More than 92% of the participants reported pain and discomfort in at least one part of their body. The major affected body part is neck, followed by the lower back and wrist. More than half of the orthodontists and oral surgeons reported that their MSDs are work-related origin. Pearson's correlation test indicated that there is a positive correlation between the current exposure and risk (r = 0.613). Multivariate regression analysis found that younger participants, male (OR = 4.1), involved physical activity (OR = 1.04), dentists not taught about ergonomics in their dental school (OR = 1.69) or never attended any workshops (OR = 1.38), who reported task involving sustained muscle contraction (OR = 1.12) or task with repetitive movements (OR = 1.11) are the major risk factors for the development of MSDs among the dentists. Conclusion: This risk assessment study found that there is a high prevalence of MSDs and WMSDs among dentists. Ergonomic awareness and health promotion need to be integrated with the professional practice for dentists.